Staphylococcus aureus agr-type vs genetic background: molecular signatures determining differential metabolism and virulence potential - Mariane Pivard; Julian Bär; Tomas Demeter; Srikanth Mairpady Shambat; Annelies S. Zinkernagel (PLoS ONE, 2026)
In Staphylococcus aureus , the quorum‑sensing accessory gene regulator ( agr ) system is the major virulence regulator. The four agr ‑types (I-IV) have been associated with distinct infection outcomes, but their direct contribution to virulence regulation and metabolism has remained unresolved due to tight linkage between agr ‑type and genetic background. To disentangle agr ‑type‑specific effects, we used congenic Newman strains in which the native agr -locus has been replaced with each of the four agr -types, alongside a Δ agr mutant. We performed RNA‑sequencing during early exponential (1h30), late exponential (6h), and stationary (12h) growth phases. Despite similar growth kinetics, agr ‑types displayed distinct activation profiles based on agrA and RNAIII expressions. Agr -I and agr -IV showed early, strong expressions, agr -II displayed intermediate expressions and agr -III initiated weak expressions only in stationary phase. This agr ‑type‑dependent activation timing was the dominant driver of global transcriptional changes. Early activation in agr ‑I and agr ‑IV induced robust expression of phenol‑soluble modulins, capsule biosynthesis genes, and pore‑forming toxins, whereas agr ‑II and agr ‑III expressed delayed or alternative virulence pathways, including upregulation of superantigen‑like genes. Among all types, agr ‑IV exhibited the broadest transcriptional response, encompassing both virulence and metabolic pathways, including differential regulation of nucleotide and fructose metabolisms. Pairwise differential expression, over‑representation analysis, and gene‑set enrichment consistently revealed agr ‑type‑specific virulence and metabolic programs. Agr ‑III, which activated latest and weakest, showed limited transcriptional change until stationary phase, whereas agr ‑I, agr ‑II, and agr ‑IV displayed progressively broader virulence and metabolic remodeling. Together, these findings demonstrate that agr ‑type determines virulence and metabolic gene expression profiles primarily by dictating the timing and magnitude of agr -activation, even within an identical genetic background and growth environment. This work provides a systematic framework for understanding agr ‑type‑specific regulatory strategies and their potential roles in S. aureus pathogenesis.